Peningkatan Hasil Belajar Mengubah Pecahan Biasa dan Campuran Ke Pecahan Desimaldengan Menggunakan Model Cooperatif Learning Tipe Student Team Achievement Division di Kelas IV SDN 28 Batipuah Ateh, Kabupaten Tanah Datar - Gitasari, Desrina; Ahmad, Syafri; Mayarnimar, Mayarnimar (Universitas Negeri Padang, 2020)
This research is motivated by the low learning outcomes of students in learning to change ordinary and mixed fractions to decimal fractions. The approach used in this study is a qualitative and quantitative approach. This type of research is Classroom Action Research (CAR). This research includes 1) Planning, 2) Implementation, 3) Observation and 4) Reflection, which consists of two cycles, namely in one cycle two meetings. Data collection techniques in this study were observation and tests, while the research instruments were observation sheets and tests in the form of objective questions and descriptions. The subjects in this study were students of grade IV SDN 28 Batipuah Ateh Tanah Datar District. The results of this study are a) Observation of RPP in the first cycle with a score of 80% and the second cycle with a score of 90%. b) The results of observations of teacher activity in the first cycle with a score of 85% and the second cycle with a score of 94% and on the aspects of students in the first cycle 82% and in the second cycle with a score of 94%. c) Learning outcomes of students in cycle I on cognitive, affective and psychomotor aspects with an average of 73 and on cycle II with an average of 83. From the results of the research conducted it can be concluded that by using the STAD-type cooperative learning model can increase activities and results in student learning in learning mathematics in class IV SDN 28 Batipuah Ateh Tanah Datar District.